Evaluating the Distribution of African Swine Fever Virus Within a Feed Mill Environment Following Manufacture of Inoculated Feed - C. G. Elijah; J. D. Trujillo; C. K. Jones; N. N. Gaudreault; C. R. Stark; K. R. Cool; C. B. Paulk; T. Kwon; J. C. Woodworth; I. Morozov; J. T. Gebhardt; J. A. Richt (Kansas Agricultural Experiment Station Research Reports, 2020)
With the global spread of African swine fever virus (ASFV) and evidence that feed and/or ingredients may be potential vectors for pathogen transmission, it is critical to understand the role the feed manufacturing industry may have in regard to potential distribution of this highly virulent virus. A pilot-scale feed mill consisting of a mixer, bucket elevator, and relevant spouting was constructed in the Biosafety Level-3 Ag animal room at the Biosecurity Research Institute at Kansas State University. A total of 18 different sites on the equipment and in the room were swabbed to evaluate environmental contamination before and after introduction of ASFV-inoculated feedstuff. First, a batch of feed was manufactured through the system to confirm the feed mill was ASFV negative; then a feedstuff inoculated with ASFV was added into the mixer and manufactured with other, non-infected ingredients. Ingredients were mixed and discharged through the bucket elevator. Subsequently, four additional ASFV-free batches of feed were manufactured. Environmental swabs were collected after each batch of feed was discharged with locations categorized into four zones: A) feed contact surface, B) non-feed contact surface but<3.2 feet away from feed, C) non-feed contact surface>3.2 feet from feed, and D) transient surfaces such as worker shoes. Environmental swabs were analyzed using qPCR analysis for the P72 ASFV gene in a BSL-3 laboratory setting to detect ASFV-specific DNA. Environmental swabs collected prior to ASFV inoculation of feed were negative for ASFV DNA. Environmental swabs collected after the manufacture of ASFV-inoculated feed resulted in contamination of zones A-D. Contamination levels with ASFV-DNA are reported as Ct value or genomic copy number (CN) per mL. In this setup, there was no evidence of sampling zone × batch interaction and no difference in the proportion of ASFV positive reactions between sampling location or batch of feed throughout the experiment. This indicates that once ASFV contamination entered the facility, the contamination quickly becomes widespread and persists on the environmental surfaces, even during manufacturing of subsequent batches of ASFV non-inoculated feed. Samples from transient surfaces (Zone D) had more detectable ASFV (a lower Ct value) compared to all other surfaces (P<0.05), indicating high level of ASFV contamination (high CN values). Samples collected after manufacturing sequence 3 had less detectable ASFV (a greater Ct value) compared to samples collected immediately following manufacture of the ASFV-inoculated batch of feed (P<0.05), indicating lower levels of ASFV contamination (low CN values) in subsequent repeats of the feed production process. There was evidence of a sampling zone × batch interaction for the number of genomic copies/mL (P = 0.002). For samples collected after manufacture of the ASFV-inoculated batch of feed, a lower number of ASFV genomic copies/mL (higher Ct) was observed for swabs collected from non-feed contact surfaces>3.2 feet from feed (Zone C) compared to feed contact surfaces (zone A) (P<0.05), with other surfaces (zone B and D) having no evidence of a significant difference. Following manufacturing sequences 1, 2, and 3, samples collected from the transient surfaces (zone D) had a greater number of ASFV genomic copies/mL (low Ct) detected compared to other sampling locations (P<0.05). After manufacturing sequence 4, there was no evidence of a difference in the number of detected ASFV genomic copies/mL between sampling locations (P>0.05). In summary, once ASFV was experimentally introduced into a feed manufacturing environment, the virus became widely distributed throughout the facility with only minor changes in detection frequency as subsequent batches of feed were produced.
Keywords: African swine fever virus; environmental contamination; feed mill